Household financial assets in the process of development - Patrick Honohan (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
Systematic information on household financial asset holdings in developing countries is very sparse; we review some available data and current policy debates. Although financial asset holdings by households are highly concentrated, deeper financial systems are correlated with improved income distribution. For low-income countries, the relevant question for poor households is not how much financial assets they have, but whether they have any access to financial products at all. Building on and synthesizing disparate data collection efforts by others, we produce new estimates of access percentages for over 150 countries. Across countries, access is negatively correlated with poverty rates, but the correlation is not a robust one, thus the supposed anti-poverty potential of financial access remains econometrically elusive. Despite policy focus on the value of credit instruments, it is deposit products that tend to be the first to be used as prosperity increases, before more sophisticated savings products and borrowing.
Keywords: D1; D12; D31; 330; household behaviour; asset holding; credit; income distribution; poverty; Kapitalanlage; Entwicklung; Entwicklungsländer